Strategy for Improving Source Code Compliance to a Style Guide - Becker, Pablo (2022)
This paper illustrates the evaluation and improvement of a Java source code considering the non-compliance with a selected set of items of the Google Java Style Guide. To do this, a strategy was used to understand and improve the Java source code. The strategy has activities that allow specifying non-functional requirements (characteristics and attributes) and designing and implementing measurement, evaluation, analysis, and change. The case was applied in the context of an advanced undergraduate course in System Engineering as a mandatory exam. The evaluation results of attributes' adherence to the aforementioned coding style guide and the improvement of non-compliances are discussed.